A new species of the grass-feeding leafhopper genus Amblysellus Sleesman (Hemiptera: Cicadellidae: Deltocephalinae) from western Mexico, with a checklist and key to species - Pinedo-Escatel, J. A.; Becerra-Chiron, I. M.; Torres-Moreno, R.; Pérez-Valencia, L. I. (Zootaxa, 2020)
A new Mexican leafhopper species, Amblysellus raygozai sp. nov., is described and illustrated from western Mexico. Specimens were collected over perennial grasses. A key for all recognized species within the country is provided.